2018
DOI: 10.1080/15622975.2018.1487077
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids are associated with metabolic parameters in bipolar disorder

Abstract: BD and HC did not differ in valine and isoleucine, whereas leucine was significantly lower in BD. Furthermore, correlations were found between BCAAs and anthropometric and glucose metabolism data. All BCAAs correlated with lipid metabolism parameters in females. There were no associations between BCAAs and long-term clinical parameters of BD. A negative correlation was found between valine and Hamilton Depression-Scale, and Beck Depression Inventory II, in male individuals Conclusions: Our results indicate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Indeed, elevated circulating BCAA levels predict the severity of IR (Newgard et al, 2009;Gannon et al, 2018) while limiting the uptake of tryptophan into the brain through the blood-brain barrier (BBB) by the large neutral amino acid transporter 1 (LAT1; Pardridge, 1998). Thus, the rate of 5-HT production may be affected by BCAAs, thereby leading to anxiodepressive symptoms, as shown in clinical (Fellendorf et al, 2018) and preclinical studies (Coppola et al, 2013;Scaini et al, 2014;Asor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, elevated circulating BCAA levels predict the severity of IR (Newgard et al, 2009;Gannon et al, 2018) while limiting the uptake of tryptophan into the brain through the blood-brain barrier (BBB) by the large neutral amino acid transporter 1 (LAT1; Pardridge, 1998). Thus, the rate of 5-HT production may be affected by BCAAs, thereby leading to anxiodepressive symptoms, as shown in clinical (Fellendorf et al, 2018) and preclinical studies (Coppola et al, 2013;Scaini et al, 2014;Asor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dalkner et al also observed increased fat craving in males vs. females with BD (43). In line with this, Fellendorf et al found a decrease of the branched chain amino acid leucine in BD compared to controls and associations between leucine, valine, isoleucine, and anthropometric as well as glucose metabolism in the BD cohort (68).…”
Section: Introductionmentioning
confidence: 75%
“…BCAA metabolism contributes to the synthesis of new glutamate when this amino acid becomes depleted in the neurons in response to oxidative stress, and therefore, this process plays a crucial role in brain function homeostasis [ 75 ]. The levels of BCAA, leucine, isoleucine, and Val are decreased in patients suffering from psychiatric disorders such as major depressive disorder, immune-related major depression, and bipolar disorder [ 76 , 77 , 78 ]. BCAA levels are also elevated in the hippocampus after antidepressant treatment [ 79 ].…”
Section: Discussionmentioning
confidence: 99%